Malaysia and the Knowledge Economy : Building a World Class Higher Education System - World Bank (Washington, DC, 2012)
This report assesses and analyzes the current state of the Malaysian university system and makes recommendations on ways to further strengthen existing higher education institutions. It looks in particular at the policy framework needed to support the growth and development of the higher education system which include the legal framework, quality assurance systems, incentives for investment, R&D policies, financing mechanisms that help low income students access education, and public financing programs that direct subsidies to strategically important institutions or fields of study. This report aims to identify key challenges and appropriate solutions which could constitute relevant policy advice for the Government of Malaysia. It concentrates on the higher education sector, including both public and private universities. Notwithstanding the overall focus on the university sector, the study makes occasional reference to the wider concept of tertiary education system as needed. It also makes reference to the broader concept of a national innovation system (NIS), and devotes considerable attention to a number of critical issues related specifically to the way that improvements in the performance of higher education institutions can lead to an overall better performance of the NIS. The report is organized into two main parts. It starts with a diagnosis of the present situation, relying on a range of key indicators to benchmark Malaysia's national innovation and higher education systems against select OECD and East Asian countries and on an in-depth analysis of the universities' main strengths and areas of weaknesses. The second part provides policy recommendations and detailed action plans to improve the Malaysian higher education system, with special attention paid to the research and innovation nexus, graduate employment, quality assurance systems, financing mechanisms, and the governance and management framework.